2019
DOI: 10.3390/en12193724
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Photoperiods on Microalgae Biofilm: Photosynthetic Performance, Biomass Yield, and Cellular Composition

Abstract: Microalgae have immense potential as biological sources to produce biofuels and high-value biomolecules. Biofilm-based microalgae cultivation has attracted much interest recently because of its high biomass productivity, reduced water use, and low cost of harvesting. This study aimed to understand the effect of photoperiod on three microalgae biofilms, including Nannochloris oculata, Chlorella sp., and Chlorella pyrenoidosa. The examined photoperiods were 3:3 s, 5:5 s, 30:30 min, 12:12 h (light-period-to-dark-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
(47 reference statements)
1
13
0
Order By: Relevance
“…Figure S3 shows the lipids, proteins and carbohydrates contents for the C. ellipsoidea and C. pyrenoidosa cultured under different LEDs. It was found that the main organic components in the microalgae represented approximately 80% of microalgae dry biomass, which were consistent with the literature [35]. Based on the cellular composition and power consumption of different LEDs, we determined the conversion capabilities of LED power-to-lipid, power-to-protein, and power-to-carbohydrate.…”
Section: The Led Power Conversion Capability Of Microalgae Biofilmsupporting
confidence: 85%
See 1 more Smart Citation
“…Figure S3 shows the lipids, proteins and carbohydrates contents for the C. ellipsoidea and C. pyrenoidosa cultured under different LEDs. It was found that the main organic components in the microalgae represented approximately 80% of microalgae dry biomass, which were consistent with the literature [35]. Based on the cellular composition and power consumption of different LEDs, we determined the conversion capabilities of LED power-to-lipid, power-to-protein, and power-to-carbohydrate.…”
Section: The Led Power Conversion Capability Of Microalgae Biofilmsupporting
confidence: 85%
“…Then, these filtration membranes were put into the biofilm culture bioreactors (polymethyl methacrylate chambers: 400 × 200 × 200 mm), containing the BG-11 culture medium solidified with 1% agar (see Supplementary Materials Tables S1 and S2 for the details) [34]. As shown in Figure 1, these bioreactors were placed into an incubator to maintain a proper temperature (25 ± 1 • C) for microalgae growth [35]. The inside of these bioreactors was aerated with compressed air enriched with 1% CO 2 (vol/vol) at a rate of 0.1 VVM (volume of air per volume of culture per minute).…”
Section: Microalgae Biofilm Culturementioning
confidence: 99%
“…This led to photoinhibition, reducing the microalgal biomass productivity [118]. The short timescale of photoperiods can be efficient to enhance the microalgal biofilm formation in relation to the photosynthetic electron transfer chain reaction, influencing the microalgal photosynthetic performance [120]. Zhang et al [120] and Martín-Girela et al [121] proved in their research that Nannochloris oculata, Chlorella pyrenoidosa, and Chlorella sp.…”
Section: Effect Of Photoperiod and Light Intensity On Attached Microalgal Growthmentioning
confidence: 99%
“…Microalgae are photosynthetic organisms that use light, carbon dioxide, and water to produce food in the form of biological macromolecules like proteins, lipids, and carbohydrates (Morales et al, 2019). Light and photoperiod affect the growth and yield of microalgae during cultivation (Ahmad et al, 2020;Zhang et al, 2019). In addition, the period of light and dark exposure until the saturation point at which the maximal photosynthetic rate is reached may control cellular contents (Darvehei et al, 2018;Sirisuk et al, 2018), including chlorophyll and antioxidants (Maroneze et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Up until now, most of the research conducted with microalgae focused on biomass production (Che et al, 2019;Kato et al, 2019;Ren et al, 2020;Vendruscolo et al, 2019;Zhang et al, 2019) and determination of the cellular contents such as lipid (Che et al, 2019;Kato et al, 2019;Medved et al, 2020;Ren et al, 2020;Vendruscolo et al, 2019;Zhang et al, 2019), fatty-acid (Che et al, 2019;Kato et al, 2019;Vendruscolo et al, 2019), chlorophyll (Gonzalez-Camejo et al, 2019;Patel et al, 2019;Vendruscolo et al, 2019), protein (Medved et al, 2020;Vendruscolo et al, 2019;Zhang et al, 2019), and carbohydrate content (Chong et al, 2019;Kato et al, 2019;Medved et al, 2020) upon the variations in the light and dark exposure. The role of photoperiods in the development of antioxidants and their responses to microalgae, however, is poorly understood.…”
Section: Introductionmentioning
confidence: 99%